The Concept of Substantive Justice in Islamic Criminal Adjudication: A Doctrinal Analysis - Najemi, Andi; Fathoni, M. Kamal (Gemini Littera Publishing, 2026)
Crimes against life represent the most serious violations of legal and moral order, demanding judicial reasoning that transcends procedural legality. In Islamic law, the protection of life (ḥifẓ al-nafs) constitutes a core objective of maqāṣid al-sharīʿah, positioning homicide not merely as a criminal offense but as a profound ethical and social transgression. This article examines judicial reasoning in adjudicating crimes against life from an Islamic law perspective, focusing on how substantive justice is constructed through judicial interpretation. Employing a normative legal research method with a judicial decision based approach, the study analyzes two Indonesian Supreme Court decisions, Decision No. 1282 K/Pid/2020 and Decision No. 813 K/Pid/2023 as primary legal materials. These rulings are examined to explore how judges assess intent, betrayal, and moral blameworthiness within the framework of positive criminal law. The findings reveal that judicial reasoning operates as a critical site of legal meaning-making, where statutory provisions are mediated through evaluative judgments concerning ethical gravity, relational harm, and proportional punishment. While Decision No. 1282 K/Pid/2020 demonstrates a stronger orientation toward substantive justice by incorporating moral considerations such as betrayal, Decision No. 813 K/Pid/2023 reflects a more restrained, procedural approach. From an Islamic law perspective, these variations highlight the normative potential of ijtihād qaḍāʾī in aligning adjudication with ethical responsibility and social justice. This study contributes to Islamic legal studies and judicial scholarship by positioning court decisions as arenas for substantive justice formation and by offering normative insights to strengthen value-oriented adjudication in cases involving the fundamental right to life.